IMPLEMENTASI MASSAGE AROMATERAPI LAVENDER DALAM MANAJEMEN NYERI NEUROPATI DIABETIK - Dahlia Purba; Aureliya Hutagaol (Jurnal Ilmiah Keperawatan IMELDA, 2026)
Diabetes mellitus is a chronic disease that is often accompanied by diabetic neuropathy complications, one of the main symptoms of which is chronic neuropathic pain. Uncontrolled pain can reduce quality of life, especially in the elderly. Various limitations of pharmacological therapy have prompted the need for safe and applicable non-pharmacological interventions, one of which is lavender aromatherapy massage.This study aims to determine the effectiveness of lavender aromatherapy massage in reducing pain intensity in elderly people with diabetes mellitus. This study used a quasi-experimental design with a non-equivalent control group pretest-posttest design. This study was conducted at H. Adam Malik Central Hospital in October 2025. The sample consisted of 70 respondents divided into an intervention group and a control group, each with 35 respondents. The intervention group received lavender aromatherapy massage three times a week for four weeks, while the control group received standard care. Pain intensity was measured using the Visual Analog Scale (VAS). Data analysis was performed using paired t-tests and independent t-tests. The results showed a significant decrease in pain intensity in the intervention group after lavender aromatherapy massage (p < 0.05), while no significant changes were found in the control group (p > 0.05). A post-test comparison between the intervention group and the control group also showed a statistically significant difference (p < 0.05). It was concluded that lavender aromatherapy massage is effective in reducing pain intensity in elderly people with diabetes mellitus. This intervention can be considered as a complementary therapy in nursing care to help improve patient comfort and quality of life.